Application method influences the oxidation rate of biologically and chemically produced elemental sulfur fertilizers. Issue 3 (11th May 2021) - Fontaine, Doline; Eriksen, Jørgen; Sørensen, Peter; McLaughlin, Michael J.; Degryse, Fien
Abstract: Elemental sulfur (ES) is commonly used as a fertilizer S source but needs to be oxidized to sulfate to become plant‐available. We assessed how placement (surface applied or incorporated) affects the oxidation of ES fertilizers. The fertilizers included an ES powder, a suspension of biogenic ES particles, and three granular fertilizers: two ES–bentonite pastilles and one monoammonium phosphate fertilizer cogranulated with ES. The fertilizers were applied either on the surface (broadcast) or incorporated into two different soils in a column experiment, incubated at 25 °C. Prior to broadcasting, the granular fertilizers were dispersed in water for 48 h to simulate the effect of 30 to 40 mm of precipitation. The columns were leached weekly and the concentration of sulfates derived through ES oxidation was measured in the leachates. The half‐lives of oxidation for the ES powder were 76 and 111 d for the incorporation and broadcast applications, respectively. The diluted biological ES suspension showed faster oxidation (8 and 30 d for incorporated and broadcast), probably because of its smaller particle size. Unlike the ES particles, the ES oxidation rates of the granular fertilizers were higher for the broadcast application than when incorporated in soil, particularly when they dispersed easily. One type of ES pastille showed little dispersion and its estimated half‐life of oxidation was >1, 000 d even when broadcast. Overall, the results show that ES oxidation depends on the degree of dispersion in the soil and that this is strongly affected by the fertilizer type and application method. Core Ideas: Particulate & granular elemental S (ES) fertilizers may be broadcast or incorporated. Broadcast granular ES fertilizers are dispersed under rainfall. Granular ES fertilizers oxidized faster when broadcast than incorporated into the soil. The oxidation rate was proportional to the degree of dispersion of the granules. Biogenic ES fertilizers oxidized four to seven times faster than powdered ES.